Хаотична та випадкова складові у природних часових даних - Bondarenko, V. G. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2015)
We proposed a method for determining the ratio of deterministic and stochastic components for observed real data. We illustrated a number of numerical experiments which used simulation modelling of the logistic chaotic sequence and the values of fractional Brownian motion with different values of Hurst exponent H. In the additive mixture, the ratio of the energies of deterministic and random components are defined. The chaotic term turns out to be more aggressive for large values of Hurst exponent: the control statistics of the mixture are different from the reference values corresponding to the fractional Brownian motion. Another situation takes place for small values of H (antipersistent case). The considered examples of time series data are described by an antipersistent model.